“Stories of Making and Unmaking”: Deep Time and the Anthropocene in New Nature Writing - Player, Amy (Text Matters: A Journal of Literature, Theory and Culture, 2022)
New Nature Writing reflects many of the anxieties which are becoming increasingly prevalent in the Anthropocene, an era which necessitates temporal leaps between the present moment, the deep past, and the deep future. Coming to contextualize our impact on the planet in the Anthropocene era in such expansive, geological terms poses profound challenges to the ways we have conventionally framed our wider place on Earth. When viewed through the lens of deep time, our impact on the planet has been comparatively brief, but we are scarcely beginning to comprehend its lasting effects. While the scale of the environmental problems we have created often seems insurmountable, this chapter argues that writing which helps us to think about deep time and acclimatizes us to its vast scale can itself serve as a way for us to grapple with the immensity of the problems we face. Through a consideration of the writing of new nature writers Robert Macfarlane and Kathleen Jamie, it looks at how their engagements with deep time challenge the feelings of helplessness that the scale of the environmental crisis can sometimes burden us with. By arguing that coming to terms with the Anthropocene is to come to terms with a changing narrative we tell ourselves about our role on the planet, it considers how New Nature Writing is playing a crucial role in this narrative shift more specifically, as it explores different ways for us to reimagine our relationship with the more-than-human world in the Anthropocene era.